2011
DOI: 10.1890/es10-00186.1
|View full text |Cite
|
Sign up to set email alerts
|

Landscape position and habitat polygons in a dynamic coastal environment

Abstract: Abstract. In contrast to stable inland systems, coastal landscape positions are dynamic, changing as shorelines migrate and storms alter topography. We define landscape position by distance to ocean shoreline and elevation above sea level, two metrics that integrate a suite of environmental and biotic factors. As shoreline and elevation change, suitability of a geo-referenced position for a given plant species may also change. The objectives of our study were to use two methods for measuring landscape position… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
69
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 53 publications
(72 citation statements)
references
References 62 publications
3
69
0
Order By: Relevance
“…Ammophila breviligulata is adapted to the dune environment and actually dependent on moving sand and burial to maintain vigorous populations (Maun and Lapierre 1984). While we did not measure sand supply rates directly, we did use wind speed, distance from shore, and dune height as surrogate measures of sand supply (Young et al 2011). None of these factors were significantly associated with tiller density, in contrast to some other studies on dunes placing more significance to wind on the presence or absence of vegetation (e.g., Wilson and Sykes 1999, Miller et al 2008, Fenu et al 2013.…”
Section: Discussionmentioning
confidence: 99%
“…Ammophila breviligulata is adapted to the dune environment and actually dependent on moving sand and burial to maintain vigorous populations (Maun and Lapierre 1984). While we did not measure sand supply rates directly, we did use wind speed, distance from shore, and dune height as surrogate measures of sand supply (Young et al 2011). None of these factors were significantly associated with tiller density, in contrast to some other studies on dunes placing more significance to wind on the presence or absence of vegetation (e.g., Wilson and Sykes 1999, Miller et al 2008, Fenu et al 2013.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies of dune-building grasses have demonstrated that sand deposition is an important factor controlling dune grass growth (e.g., van der Valk, 1974;Maun, 1998;Maun and Perumal, 1999;Dech and Maun, 2005). Other factors include salinity and water availability, for which Young et al (2011) use distance from shoreline and elevation as proxies. Other factors include salinity and water availability, for which Young et al (2011) use distance from shoreline and elevation as proxies.…”
Section: Introductionmentioning
confidence: 99%
“…Predictive models including some or all of these factors have been applied to wetlands (Geselbracht et al, 2011;Rogers, Saintilan, and Copeland, 2012;Stralberg et al, 2011;Traill et al, 2011), mangrove forests (Doyle et al, 2010;Woodroffe, 1990), dune systems (Young et al, 2011), and tidal freshwater forests (Doyle et al, 2010). Some studies have modeled the effects of saltwater intrusion on groundwater salinity (Sherif and Singh, 1999;Werner and Simmons, 2009).…”
Section: Introductionmentioning
confidence: 99%